The prevalence of functional absence of flexor digitorum superficialis to the little finger: A study in a Turkish population. Issue 3 (June 2013) - Guler, Ferhat; Kose, Ozkan; Turan, Adil; Baz, Ali Bulent; Akalın, Serdar
Abstract This prospective study was conducted to determine the prevalence of absence of flexor digitorum superficialis (FDS)-V tendon and to investigate the clinical usefulness of symmetry patterns, differences between sex, laterality, and dexterity in a Turkish population. Four hundred randomly-selected adult patients were examined for the absence of FDS-V function. The absence of FDS-V on both sides, results of the examination tests, age, sex, and dexterity were recorded and analysed statistically. The overall prevalence of absence of FDS-V was 18.5% in the Turkish population. The prevalence of functional absence of FDS-V was statistically similar between the body sides and sex (p = 0.258 and p = 0.333). The prevalence of symmetric occurrence of the variations in both hands was 87.2%. If a functional FDS is demonstrated in one hand, the probability of having a functional FDS-V in the contralateral hand is 91.8%. However, when the FDS-V is absent in one hand, the probability of having an absent FDS-V in the contralateral hand is 51.1%. The symmetric occurrence of variations was equally distributed in both sex and dexterity (p = 0.223 and p = 0.201). Prediction of FDS-V function in one hand through examining the opposite hand may cause false negative or false positive results. However, if the uninjured hand has independent FDS-V function, the inability to flex the PIP joint in the injured hand can be accepted as an injury to the FDS and surgical exploration should be performed. However, if the uninjured hand has an absent function, assumption of symmetric distribution should not be used.